PETROLOGY AND GEOCHEMISTRY OF ECLOGITE XENOLITHS FROM THE COLORADO PLATEAU: IMPLICATIONS FOR THE EVOLUTION OF SUBDUCTED OCEANIC CRUST - Usui T.; Nakamura E.; Helmstaedt H. (My University, 2006)
Eclogite xenoliths from the Colorado Plateau, interpreted as fragments of the subducted Farallon plate, are used to constrain the trace element and Sr–Nd–Pb isotopic compositions of oceanic crust subducted into the upper mantle. The xenoliths consist of almandine-rich garnet, Na-clinopyroxene, lawsonite and zoisite with minor amounts of phengite, rutile, pyrite and zircon. They have essentially basaltic bulk-rock major element compositions; their Na2O contents are significantly elevated, but K2O contents are similar to those of unaltered mid-ocean ridge basalt (MORB). These alkali element characteristics are explained by spilitization or albitization processes on the sea floor and during subduction-zone metasomatism in the fore-arc region. The whole-rock trace element abundances of the xenoliths are variable relative to sea-floor-altered MORB, except for the restricted Zr/Hf ratios (36·9–37·6). Whole-rock mass balances for two Colorado Plateau eclogite xenoliths are examined for 22 trace elements, Rb, Cs, Sr, Ba, Y, rare earth elements, Pb, Th and U. Mass balance considerations and mineralogical observations indicate that the whole-rock chemistries of the xenoliths were modified by near-surface processes after emplacement and limited interaction with their host rock, a serpentinized ultramafic microbreccia. To avoid these secondary effects, the Sr, Nd and Pb isotopic compositions of minerals separated from the xenoliths were measured, yielding 0·70453–0·70590 for 87Sr/86Sr, ?3·1 to 0·5 for ɛNd and 18·928–19·063 for 206Pb/204Pb. These isotopic compositions are distinctly more radiogenic for Sr and Pb and less radiogenic for Nd than those of altered MORB. Our results suggest that the MORB-like protolith of the xenoliths was metasomatized by a fluid equilibrated with sediment in the fore-arc region of a subduction zone and that this metasomatic fluid produced continental crust-like isotopic compositions of the xenoliths.
Keywords: Colorado Plateau; eclogite xenolith; geochemistry; subducted oceanic crust